Literasi Matematika Siswa Sekolah Dasar Ditinjau dari Gaya Kognitif Field Independent - Rima Qoriawati; Ida Sulistyawati; Via Yustitia (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Mathematics literacy is a person's ability to solve contextual problems through the application of mathematics, the importance of mathematical literacy is applied so that students can use the mastery of mathematical concepts to solve problems faced. This study aims to (1) To find out the math literacy skills of grade 4 students at SDN Menanggal 601 Surabaya with field independent (FI) cognitive style, This research method uses qualitative method with case study approach. The subjects in this study were four students who were randomly selected based on criteria and obtained students with cognitive style (FI) at SDN Menanggal 601 Surabaya. Data collection techniques used are filling out questionnaires, providing tests on mathematical literacy of fractional material and interviews. The analysis techniques used are processing data, coding and interpreting data. To check the validity of the data researchers conducted a triangulation test of investigators and techniques.The results obtained is Students with an independent field cognitive style on indicators identify information and are able to write down things that are known and asked from the questions and explain clearly when conducting interviews with researchers and on indicators concluding problems are able to write conclusions obtained from questions on the answer sheet and answer interview descriptions clearly.